Two novel C-terminal frameshift mutations in the β-globin gene lead to rapid mRNA decay - Katarzyna Rawa; Roman J. Szczesny; Ewelina P. Owczarek; Anna Adamowicz-Salach; Anna Klukowska; Urszula Demkow; Danuta Plochocka; Pawel Szczesny; Monika Gora; Andrzej Dziembowski; Beata Burzynska (BMC, 2017)
Abstract Background The thalassemia syndromes are classified according to the globin chain or chains whose production is affected. β-thalassemias are caused by point mutations or, more rarely, deletions or insertions of a few nucleotides in the β-globin gene or its immediate flanking sequences. These mutations interfere with the gene function either at the transcriptional, translational or posttranslational level. Methods Two cases of Polish patients with hereditary hemolytic anemia suspected of thalassemia were studied. DNA sequencing and mRNA quantification were performed. Stable human cell lines which express wild-type HBB and mutated versions were used to verify that detected mutation are responsible for mRNA degradation. Results We identified two different frameshift mutations positioned in the third exon of HBB. Both patients harboring these mutations present the clinical phenotype of thalassemia intermedia and showed dominant pattern of inheritance. In both cases the mutations do not generate premature stop codon. Instead, slightly longer protein with unnatural C-terminus could be produced. Interestingly, although detected mutations are not expected to induce NMD, the mutant version of mRNA is not detectable. Restoring of the open reading frame brought back the RNA to that of the wild-type level. Conclusion Our results show that a lack of natural stop codon due to the frameshift in exon 3 of β-globin gene causes rapid degradation of its mRNA and indicate existence of novel surveillance pathway.